Antithrombotic Activity of SR 46349, a Novel, Potent and Selective 5-HT2 Receptor Antagonist - Herbert, J M; Bernat, A; Barthelemy, G; Dol, F; Rinaldi, M (Thrombosis and Haemostasis, 1993)
SR 46349 (trans-4-[(3Z)3-(2-dimethylaminoethyl)oxyimino-3(2-fluorophenyl)propen-1-yl] phenol, hemifumarate) is the first member of a newly-developed 5-HT2 antagonist series. SR 46349 potently inhibited serotonin-induced aggregation of rabbit and human platelets (IC50 = 1 and 3.9 nM respectively) but had no effect on the action of other platelet aggregating agents. SR 46349 was 118 and 25 times more potent than ketanserin against 5-HT + epinephrine-induced aggregation of rabbit and human platelets respectively.A single per os administration of SR 46349 (1 mg/kg) resulted in a strong inhibition of 5-HT + epinephrine-induced platelet aggregation in the rabbit as measured ex vivo (67% inhibition, 6 h after the administration). Intravenous or oral administration of SR 46346 inhibited in a dose-dependent manner venous thrombosis induced by ligature of the jugular vein of rabbits whose blood was made hypercoagulable by i.v. administration of tissue thromboplastin. The doses of SR 46349 which inhibited 50% of thrombus formation were 1.5 ± 0.8 mg/kg and 17 ± 0.5 mg/kg after i.v. or oral administration respectively. When given i.v. to rabbits, SR 46349 exhibited a dose-dependent antithrombotic effect in an arterio-venous shunt model. Significant increase of the bleeding time was observed after the i.v. administration of 5 mg/kg of SR 46349 (3-fold increase). In dogs, SR 46349 inhibited cyclic coronary artery blood flow variations, complete abolition of CFVs being achieved after the i.v. administration of 0.5 mg/kg.In conclusion, SR 46349 is a highly potent, selective antagonist of serotonin in vitro and is to be considered as a potent, orally active antithrombotic agent.